THE ROLE OF THE SOCIAL WORKER IN THE PREVENTION OF CHILD TRAFFICKING IN SOUTH AFRICA - Sambo, Juliet Patience; Spies, Gloudien (Social Work/Maatskaplike Werk, 2012)
According to the United Nations Palermo Protocol (2000:14), child trafficking is defined as the recruitment, transportation, transfer, harbouring or receipt of children through threats, force, coercion, abduction, fraud and/or deception. Child trafficking takes many different forms. Some children are forcibly abducted, others are tricked and still others opt to be trafficked, seduced by the promise of earnings, but unaware of the level of exploitation they will go through at the end of the recruiting chain. Child trafficking always involves a journey, whether within the country or across the border. At the final destination trafficked children become part of the underworld of criminality and illegality into which they are plunged (United Nations Children Fund, 2005:49).